Test the effectiveness of Breadfruit (Artocarpus altilis) leaf extract on the growth of Staphylococcus aureus - Fitrotin Azizah; Anindita Riesti Retno Arimurti; Dita Artanti; Yeti Eka Sispita Sari (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
Infectious diseases caused by Staphylococcus aureus are a health problem in Indonesia. Antibiotics can be used as the treatment, but currently Staphylococcus aureus is resistant to antibiotics. Therefore, it is necessary to find alternative medicine. One of the plants that has characteristics to be used as herbal medicine is Breadfruit leaves. The purpose of this study was to determine the effect of concentration on breadfruit leaf juice which can inhibit the growth of Staphylococcus aureus bacteria. This type of research is experimental. The study population was pure Staphylococcus aureus bacteria on NAS (Nutrient Agar Slant) media. The sample in this study was pure Staphylococcus aureus transferred from pure culture media (NAS), while the number of repetitions of the sample was 5 times the treatment, in this study were P1 (100%), P2 (75%), P3 (50%), P4 (25%), P5(0%). Data on the growth of Staphylococcus aureus bacteria was obtained by indirect observation, namely through laboratory tests and data collection techniques using the ANOVA test with an error rate (0.05) and followed by the Tukkey HSD test through the SPSS16.0 program. Based on the results of the antibacterial test of breadfruit leaf juice (Artocarpus altilis) in the ANOVA test, the probability number was 0.000 and there was an effect on the growth of Staphylococcus aureus bacteria. Followed by the Tukkey HSD test, it was obtained at a concentration of 25% which is the minimum inhibitory power, the effective concentration to inhibit the growth of Staphylococcus aureus at a concentration of 75%. From the data above, it can be concluded that there is an effect of breadfruit leaf juice (Artocarpus altilis) on the growth of Staphylococcus aureus.©2020 JNSMR UIN Walisongo. All rights reserved.